Exploring association of mobile phone access with positive health outcomes and behaviors amongst post-partum mothers in rural Malawi - Martina Anto-Ocrah; Ryan J. Latulipe; Tiffany E. Mark; David Adler; Tasneem Zaihra; Joseph W. Lanning (BMC, 2022)
Abstract Background Access to mass media and emerging technologies (e.g., cell phones, the internet, and social media) is a social determinant of health that has been shown to profoundly influence women's health outcomes. In the African region, where women in rural settings with limited access to care are most vulnerable to maternal mortality and other pregnancy-related morbidities, mobile phone access can be an important and life-saving health determinant. Objective The goal of this study was to examine the association between mobile/cellular phone ownership and health behaviors of post-partum mothers in rural Malawi. Methods In this cross-sectional study, we recruited and consented a convenient sample of 174 post-partum mothers of 4- and 5-month-olds who were attending well-child clinics in Gowa, situated in the rural Ntcheu district of Malawi. Using logistic regression models, we hypothesized that compared to non-cell phone owners, mobile phone ownership will be predictive (greater odds) of antenatal visit frequency, exclusive breastfeeding knowledge and practices, health-seeking behaviors, and involvement in motherhood support groups; and protective (lower odds) of infant illnesses, breastfeeding challenges, and post-partum depressive symptoms. Results Mobile phones were highly prevalent in this rural setting, with 45% (n = 79) of post-partum women indicating they owned at least one cell phone. Cell phone owners tended to have higher levels of education (p < 0.012) and wealth (p < 0.001). Interestingly, mobile phone ownership was only associated with exclusive breastfeeding practices; and phone owners had 75% lower odds of exclusively breastfeeding (adj. OR 0.25; 95% CI: 0.07-0.92, p = 0.038) in multivariable models. Though not statistically significant but clinically meaningful, cell phone ownership was associated with fewer depressive symptoms (adj. OR 0.84; 95% CI: 0.39-1.84, p = 0.67) and more social support (adj. OR 1.14; 95% CI: 0.61-2.13, p = 0.70). Conclusions Digital literacy and internet connectivity are social determinants of health, thus delving deeper into mothers' digital experiences to identify and ameliorate their unique barriers to full digital access will be crucial to successful implementation of digital interventions to address post-partum challenges for women in hard-to-reach settings such as ours. Such interventions are of even greater relevance as the Covid-19 pandemic has increased the urgency of reaching vulnerable, marginalized populations.